Analyzing the Effects of Inflation, Islamic Financing, and the Maqasid al-Sharia Index on Indonesia’s Economic Growth - Muhamad Gunawan; Setia Mulyawan (Islamicate Institute, 2026)
This study aims to analyze the influence of inflation, Islamic financing, and the Maqosid Al Syariah Index on economic growth in Indonesia during the 2020-2025 period. The background of this research is based on the aspect of macroeconomic stability and the role of the Islamic financing system in supporting the equitable distribution of sustainable economic development. Inflation is an indicator of price stability, Islamic financing as an intermediary instrument of financing based on Islamic values, and the Maqosid Al Sharia Index as a measure of the achievement of sharia goals in economic development, are the main variables in this study. The method used is a quantitative approach with a double linear regression analysis technique. Secondary data is taken from official publications of Bank Indonesia, the Financial Services Authority, the Central Statistics Agency, and the Maqosid Al Syariah index which are then developed by related institutions. This study examines the relationship between independent variables (inflation, islamic financing, and the Maqosid Al Syariah index) and the dependent variable, namely Gross Domestic Product (GDP) growth as an indicator of economic growth. The results show that inflation has a significant negative influence on economic growth, which shows that price increases in general can reduce purchasing power and hinder economic activity. On the other hand, Islamic financing has a significant positive effect, reflecting the active role of Islamic financial institutions in supporting the real sector and increasing productivity. Meanwhile, the Maqosid Al Sharia Index also shows a positive influence, showing that the achievement of sharia goals such as the protection of life, intelligence, property, heredity, and religion also contributes to inclusive and sustainable economic development. This study concludes that the integration between macroeconomic policies and strengthening the Islamic financial system based on Maqosid Al Sharia can be an effective strategy in encouraging Indonesia's economic growth in the future. These findings are expected to serve as a reference for policy makers, academics, and practitioners of sharia economics in designing policies that are more responsive and oriented towards community welfare.